2022
DOI: 10.1101/2022.01.05.21268478
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporary hold of mycophenolate boosts SARS-CoV-2 vaccination-specific humoral and cellular immunity in kidney transplant recipients

Abstract: Transplant recipients exhibit an impaired protective immunity after SARS-CoV-2 vaccination, potentially caused by mycophenolate (MPA) immunosuppression. Recent data from autoimmune patients suggest that temporary MPA hold might significantly improve booster vaccination outcomes. We applied a fourth dose of SARS-CoV-2 vaccine during temporary (5 weeks) MPA hold to 29 kidney transplant recipients, who had not mounted a humoral immune-response to previous vaccinations. Seroconversion until day 32 after vaccinatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 43 publications
3
15
1
Order By: Relevance
“…In a preprint format, Schrezenmeier et al reported the result of a study assessing a fourth dose BNT162b2 vaccine in 29 kidney transplant recipients who did not seroconvert with the three first doses of the vaccine and were on MMF (152). The fourth dose was administered 4-7 days after MMF hold and MMF was paused until day 28-35 after vaccination.…”
Section: Fourth Dose Vaccinationmentioning
confidence: 99%
“…In a preprint format, Schrezenmeier et al reported the result of a study assessing a fourth dose BNT162b2 vaccine in 29 kidney transplant recipients who did not seroconvert with the three first doses of the vaccine and were on MMF (152). The fourth dose was administered 4-7 days after MMF hold and MMF was paused until day 28-35 after vaccination.…”
Section: Fourth Dose Vaccinationmentioning
confidence: 99%
“…Kidney transplant recipients treated and followed at our institution received repeated doses of SARS-CoV-2 vaccines in case of sustained non-response to vaccination against SARS-CoV-2 (14). Data from up to five doses of vaccine were included in this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A third vaccination was recommended early on for KTR in order to increase immune response (13). Further, repeated vaccinations under modulated immunosuppression effectively increase protection, yet a substantial number of patients does not reach protective antibody levels (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…11 T cell response over time only changes at a functional level, never reaching the level of healthy individuals. 12,13 In summary the poor T cell response in combination with an impaired humoral response offered only a limited protection from infection and a severe course of COVID-19. 14…”
Section: Introductionmentioning
confidence: 99%
“…11 T cell response over time only changes at a functional level, never reaching the level of healthy individuals. 12,13 In summary the poor T cell response in combination with an impaired humoral response offered only a limited protection from infection and a severe course of COVID-19. 14 The question therefore arises about optimal management of non-responding patients and in particular whether repeated vaccinations increase serological response rates.…”
Section: Introductionmentioning
confidence: 99%